Phenotypical features and states of the vegetative nervous system in patients with aneurism of ascending part of aorta - Kavatsіuk O. O. (Zaporozhye Medical Journal, 2014)
Aim. Phenotypic features and vegetative balance in patients of all ages with an aneurysm of ascending aorta. Methods and results. In order to identify the underlying causes and associated factors in the development of ascending aorta aneurysm in patients of different age and its complications predictors, there were 154 patients examined for the phenotypic characteristics and the research conducted by the methods of echocardiography, ECG, ambulatory monitoring of ECG and blood pressure. Conclusion. There were irregularities of autonomic balance, mainly hypersympathicotonia. Patients of young and middle age had dystonia associated with connective tissue disorder. In older patients autonomic balance changes were associated with left ventricular hypertrophy and reduced contractile function of the heart. This suggests the possibility of using this combination of abnormalities in the evaluation of development of the aneurysm.‏